Sebaran Lokasi Potensial Minimarket (Alfamart dan Indomaret) Di Kecamatan Babelan - NIDA DIANA; SONY NUGRATAMA; adrian adrian (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2018)
District Babelan has many minimarkets in the form of Alfamart and Indomaret. Minimarket in District Babelan amounted to 43 minimarket. Minimarkets are scattered in several villages in Babelan sub-district, namely Bahagia village, Kebalen village, Babelan Kota village, Kedung Pengawas village, Kedung Jaya village and Muarabakti village. The purpose of this study is to see the development of Alfamart and Indomaret, knowing the pattern of distribution as well as potential location of minimarket establishment. The method used in this research is quantitative descriptive analysis with survey approach. Methods of data analysis using stop-point analysis. Data collection using observation techniques by taking data on location and documentation. The results of this study indicate that the development of Alfamart and Indomaret in the District of Babelan experienced rapid development from 2013-2017. In 2013 in Babelan sub-district there are only 12 minimarkets and by 2017 it has increased to 43 minimarkets, which indicates that minimarket developments in Babelan Sub-district have progressed over time. Next, the pattern of distribution Alfamart and Indomaret in District Babelan has a pattern of clumping. Other than that, the determination of potential location of minimarket establishment is needed to know where the potential position to establish minimarket. The potential distance of minimarket between villages in Babelan sub-district is not much different. The average potential distance of minimarket between villages is 1,4 km. Keywods : Minimarket, distribution pattern potential location, District of Babelan